Probiotic as an adjuvant preventive treatment for ventilator associated pneumonia: an evidence-based case report - Theresia Adareth (World Nutrition Journal, 2022)
Background and objectives : Ventilator-associated pneumonia (VAP) is one of the most frequent nosocomial infections in patients requiring mechanical ventilation. It leads to prolonged duration of mechanical ventilation and ICU stay that is associated with a high rate of mortality, and the increase of healthcare burden. There have been various attempts to reduce the incidence of VAP including the use of antibiotics, but neither of these has conclusively shown to be beneficial. Probiotics have preventive effects in VAP through the suppression of pathogenic bacteria, enhancement of innate immunity, and promotion of epithelial barrier function. This study aimed to find out the efficacy of probiotic as adjuvant preventive treatment in patients with high risk of VAP.